2022
DOI: 10.1186/s13690-022-00972-6
|View full text |Cite
|
Sign up to set email alerts
|

Interaction analysis of lipid accumulation product and family history of diabetes on impaired fasting glucose and diabetes risk in population with normotension in Eastern China: a community-based cross-sectional survey

Abstract: Background Lipid accumulation product (LAP) is considered to be a new convenient useful indicator to assess the visceral fat. Therefore, we aimed to evaluate the risk factors of impaired fasting glucose (IFG) and diabetes, and explore the possible interacting influences of LAP with other factors on the risk of IFG and diabetes among Chinese normotension adults. Methods A multistage stratified cluster sampling method was conducted to select urban re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 57 publications
0
1
0
Order By: Relevance
“…Subsequently, more studies have explored the relationship between LAP and diabetes. Overall, there is a positive correlation between LAP and diabetes risk ( 24 35 , 52 – 61 ), and LAP has been found to be effective in diagnosing/predicting diabetes ( 24 – 31 , 56 62 ). However, further differentiation between genders in the studies revealed some interesting trends, with two studies ( 26 , 27 ) showing stronger associations of LAP with diabetes in males than in females; furthermore, in a study involving the general Indonesian population ( 63 ), the cross-sectional analysis showed that LAP was associated with diabetes risk in females, while this association disappeared in the male population, and in a subsequent study of 2,427 baseline non-diabetic participants with 4-year follow-up period, LAP was not associated with the risk of future diabetes in either gender.…”
Section: Discussionmentioning
confidence: 97%
“…Subsequently, more studies have explored the relationship between LAP and diabetes. Overall, there is a positive correlation between LAP and diabetes risk ( 24 35 , 52 – 61 ), and LAP has been found to be effective in diagnosing/predicting diabetes ( 24 – 31 , 56 62 ). However, further differentiation between genders in the studies revealed some interesting trends, with two studies ( 26 , 27 ) showing stronger associations of LAP with diabetes in males than in females; furthermore, in a study involving the general Indonesian population ( 63 ), the cross-sectional analysis showed that LAP was associated with diabetes risk in females, while this association disappeared in the male population, and in a subsequent study of 2,427 baseline non-diabetic participants with 4-year follow-up period, LAP was not associated with the risk of future diabetes in either gender.…”
Section: Discussionmentioning
confidence: 97%
“…The CUT-off value of this study was 33.8 (sensitivity, 72%; specificity, 44%) in the study population, and the AUC was 0.613, which is similar to results of a couple of studies. Shu et al (2022) reported a cut-off value of 33.54 with an AUC of 0.650 (sensitivity, 54.6%; specificity, 62.42%) [ 26 ]. This study was conducted in Bengbu, Anhui Province of Eastern China.…”
Section: Discussionmentioning
confidence: 99%